Peran Motivasi Kerja dalam Memediasi Pengaruh Kompetensi dan Budaya Kerja Terhadap Kinerja Karyawan pada Implementasi Early Warning System di PT Permodalan Nasional Madani - Dindin Ismail; Siti Safaria (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2026)
This study aims to analyze and evaluate three independent variables, namely competence and organizational culture, as well as work motivation as an intervening variable for the dependent variable studied, namely the performance of Supervisory and Monitoring Implementation (PPM) employees at Permodalan Nasional Madani (PNM). The sample consists of all 105 PPM PNM employees, which is the entire sample so that there are PPM representatives for PNM Branches from a total of 58 Branches throughout Indonesia. The analysis method in this study uses SEM analysis with SmartPLS software. Work culture has the most dominant influence on employee motivation and performance. Motivation plays an important role in improving employee performance. Competence is not proven to have a significant effect on motivation or performance in the model. Motivation is proven to be a mediating variable in the relationship between work culture and performance. The research model has excellent validity, reliability, and predictive ability.